Effectiveness Of Laws In The Implementation Of Food Distribution Permit Sanctions For Food Security - Mirdedi; Jarkasi Anwar; Muhamad Muslih (Faculty of Law, University of Mataram, 2026)
In Indonesia, many food products are still circulating that are hazardous to consumer health and do not meet the criteria and requirements set out in the law regarding products that may be distributed.The purpose of this study is to determine the effectiveness of the Food Law and the Consumer Protection Law in their application to food products in circulation.The methodology used was normative sociological and normative legal juridical research, which was descriptive and analytical in nature, using primary and secondary data sources analyzed qualitatively by the researcher.The summary of the research findings is that the existence of distribution permits and supervision of distributed products is crucial for maintaining food safety. However, this still conflicts with the reality, as many products are still distributed without distribution permits. The government must be more selective in granting distribution permits and prioritize consumer protection, namely by monitoring and preventing the distribution of food products that endanger consumer health and safety. Action against violations must also be taken through sanctions in the form of business permit closures, fines, or other administrative sanctions to prevent the distribution of unlicensed products.